2008
DOI: 10.1002/ange.200705154
|View full text |Cite
|
Sign up to set email alerts
|

From an N‐Methyl N‐Heterocyclic Carbene to Carbyne and Carbide Ligands via Multiple CH and CN Bond Activations

Abstract: Mehrere zur Auswahl: Das Carbin‐C‐Atom in 1 und das Carbid‐C‐Atom in 2 stammen aus einer Methylgruppe von 1,3‐Dimethylimidazol‐2‐yliden. Die Bildung des Komplexes 1 setzt eine Aktivierung aller drei C‐H‐Bindungen der Methylgruppe voraus, und um zum Komplex 2 zu gelangen, muss zusätzlich die C‐N‐Bindung aktiviert werden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…similar to that of 2. The Os−C(1) bond lengths of 2.022 (4) and 2.029(4) Å compare well with the distances reported for other Os−imidazolylidene derivatives with normal coordination of the NHC. 20 The 1 H, 13 C{ 1 H}, and 31 P{ 1 H} NMR spectra of 3, in benzene-d 6 at room temperature, are consistent with the structure shown in Figure 3.…”
Section: ■ Results and Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…similar to that of 2. The Os−C(1) bond lengths of 2.022 (4) and 2.029(4) Å compare well with the distances reported for other Os−imidazolylidene derivatives with normal coordination of the NHC. 20 The 1 H, 13 C{ 1 H}, and 31 P{ 1 H} NMR spectra of 3, in benzene-d 6 at room temperature, are consistent with the structure shown in Figure 3.…”
Section: ■ Results and Discussionsupporting
confidence: 80%
“…1 H NMR (400 MHz, C 6 D 6 , 298 K): δ 7.53 (br, 2H, CH Ph ), 7.27 (dd, 3 J H−H = 7.6, 3 J H−H = 7.6, 2H, CH Ph ), 6.85 (t, 3 J H−H = 7.6, 1H, CH Ph ), 6.10 (s, 1H, CH imidazole ), 5.97 (s, 1H, CH imidazole ), 3.99 (s, 3H, NCH 3 ), 3.43 (s, 2H, NCH 2 ), 2.96 (br, 1 H, CHPh) 2.74−2.62 (m, 6H, PCH), 1.23 (dvt, 3 J H−H= 6.4, N = 12.8, 18H, PCH(CH 3 ) 2 ), 1.18 (dvt, 3 J H−H = 6.4, N = 12.8, 18H, PCH(CH 3 )2 ). 13 C{ 1 H}-APT NMR plus HSQC and HMBC (75.5 MHz, C 6 D 6 , 298 K): δ 308.6 (t, 2 J C−P = 12.8, OsCC), 233.7 (t, 2 J C−P = 6.8, CO), 180.0 (t, 2 J C−P = 7.6, NCN), 131.1 (t,4 J C−P = 2.3, C ipso ), 128.2 (s, CH Ph ), 126.7 (s, CH Ph ), 125.4 (s, CH imidazole ), 123.5 (s, CH Ph ), 117.0 (t, 3 J C−P = 3.8, CHPh), 116.9 (s, CH imidazole ), 74.4 (s, CH 2 ), 37.1 (s, NCH 3 ), 26.1 (vt, N = 23.4, PCH), 20.3 and 20.0 (both s, PCH(CH 3 ) 2 ). 31 P{ 1 H} NMR (162.0 MHz, C 6 D 6 , 298 K): δ −11.7 (s).…”
mentioning
confidence: 99%
“…8 Recent model studies focus on CN double‐bond cleavage of aromatic N‐heterocycles, because this process presents the promising opportunity of eliminating an expensive and energy intensive hydrogenation step 9. Ultimately, an aliphatic CN bond scission must occur, and herein we provide a relevant example of a unique CN bond activation across a WW dimer and the formation of a bridging methylidyne ligand by methyl dehydrogenation 10. This sequence of reactions represents a model pathway for site deactivation of commercial HDN catalysts.…”
Section: Methodsmentioning
confidence: 89%
“…Recent studies by our group [17] and also by those of Whittlesey [16] and Cole [18] have revealed that some imidazolederived NHCs can be incorporated into triruthenium carbonyl clusters, when the NHCs are not used in excess, [16c, 18] to give isolable derivatives of the type [Ru 3 (CO) 11 (NHC)]. These clusters are prone to undergo intramolecular C(sp 2 )ÀH, [16a,b] C(sp 3 )ÀH, [17a,c-e] and/or C(sp 2 )ÀN [17d] bond-activation processes, but only the double CÀH activation of a methyl group in [Ru 3 (CO) 11 (Me 2 Im)] (Me 2 Im = 1,3-dimethylimidazol-2-ylidene) has been mechanistically studied.…”
Section: In Memory Of Lorenzo Pueyomentioning
confidence: 98%